2017
DOI: 10.1016/j.toxrep.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arsenic acid withdrawal on hepatotoxicity and disruption of erythrocyte antioxidant defense system

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Substances that can initiate activity at the ARE include environmental pollutants, hydrogen peroxide and nitric oxide. The Nrf2-Maf-ARE complex then initiates subsequent speci c antioxidant and detoxi cation genes such as that of GST, GPx, GSH and SOD; thereby, increasing antioxidant activities and inactivating ROS (Baird and Dinkova-Kostova 2011; Oyagbemi et al 2017). The antioxidant effect of naringin was established as naringin restored the levels of GSH, GST, GP X , and SOD in the hepatic tissue of BPA-exposed chicks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substances that can initiate activity at the ARE include environmental pollutants, hydrogen peroxide and nitric oxide. The Nrf2-Maf-ARE complex then initiates subsequent speci c antioxidant and detoxi cation genes such as that of GST, GPx, GSH and SOD; thereby, increasing antioxidant activities and inactivating ROS (Baird and Dinkova-Kostova 2011; Oyagbemi et al 2017). The antioxidant effect of naringin was established as naringin restored the levels of GSH, GST, GP X , and SOD in the hepatic tissue of BPA-exposed chicks.…”
Section: Discussionmentioning
confidence: 99%
“…Birds are exposed BPA since plastic such as overhead water tanks, drinkers and feeding trays are normally utilized in poultry farms for some major activities (Escande et al 2006). Previous studies on animal models reported that BPA-induced oxidative stress caused a reprotoxic effect by affecting reproductive potential and is also hepatotoxic (Oyagbemi et al 2017;Kumar et al 2019). For instance, BPA caused sperm reserves reduction, shorter sperm transit time, and reduction in mitochondrial activity (Matuszczak et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In macroalgae, organic As appears mostly as arsenosugars and, sometimes, as methyl derivatives [monomethylarsonic acid (MMA), dimethylarsinic acid (DMA), and arsenobetaine (AsB)], while the inorganic forms are mainly represented by arsenate (AsV) and arsenite (AsIII). In general, organic forms exert low or no toxicity [ 147 , 148 ], while the inorganic are undoubtedly the most hazardous, with their accumulation being already associated to the development of several disorders, including nephrotoxicity, diabetes, hepatotoxicity, cardiovascular dysfunction, and cancer, mainly at the skin, lungs, and bladder level [ 149 , 150 , 151 , 152 ].…”
Section: Worries Related To Macroalgae Consumptionmentioning
confidence: 99%
“…Significant elevation of MDA levels in the brain and liver serves as a marker to measure tissue oxidative stress levels. It is well known that reduced glutathione (GSH) is involved in protection of normal cell structure and functions by maintaining the redox homeostasis, quenching free radicals and by participating in detoxification reactions [57]. GSH is a major endogenous antioxidant which counter balances free radical mediated damage.…”
Section: Discussionmentioning
confidence: 99%